Le rôle attribué par les étudiants aux études : un utilitarisme dominant ? - Florian Olivier (Cahiers de la Recherche sur l'Education et les Savoirs)
From the competition for social positions which pushes students to rationalize their choice of orientation, to the recurrent transformations of higher education, reflecting ever-increasing demands for professionalization, studies are increasingly thought under the pragmatic framework of their practical effectiveness: studies would be, above all, the means, the solution, for a successful integration of young people into the professional world. Whether or not the appropriateness of this normative vision of studies needs to be questioned, it is clear that from the student’s point of view, things are more complex: from one field of study to another, from the beginning to the end of studies, the normative postures with which the studies are envisaged vary widely.